Advance care planning in Australia during the COVID‐19 outbreak: now more important than ever. Issue 8 (6th August 2020) - Sinclair, Craig; Nolte, Linda; White, Ben P.; M. Detering, Karen
Abstract: The novel Coronavirus disease 2019 (COVID‐19) outbreak has led to rapid and profound changes in healthcare system delivery and society more broadly. Older adults, and those living with chronic or life‐limiting conditions, are at increased risk of experiencing severe or critical symptoms associated with COVID‐19 infection and are more likely to die. They may also experience non‐COVID‐19 related deterioration in their health status during this period. Advance care planning (ACP) is critical for this cohort, yet there is no coordinated strategy for increasing the low rates of ACP uptake in these groups, or more broadly. This paper outlines a number of key reasons why ACP is an urgent priority, and should form a part of the health system's COVID‐19 response strategy. These include reducing the need for rationing, planning for surges in healthcare demand, respecting human rights, enabling proactive care coordination and leveraging societal change. We conclude with key recommendations for policy and practice in the system‐wide implementation of ACP, to enable a more ethical, coordinated and person‐centred response in the COVID‐19 context.